2023
DOI: 10.1039/d2tc04529j
|View full text |Cite
|
Sign up to set email alerts
|

The race between complicated multiple cation/anion compositions and stabilization of FAPbI3 for halide perovskite solar cells

Abstract: Compositional modifications and passivating additives have been key enablers to approach operationally stable halide perovskite devices with excellent optoelectronic properties. Thermal and structural instability of the most desirable single-cation metal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“…Furthermore, the influence of the A-site cation on the band gap is less direct compared to that of the X-site and B-site ions, aligning with our observed results for the band gap. 39 The surface morphology of K + -doped FAPbI 3 films was characterized using atomic force microscopy (AFM) (see Figure S8). The root-mean-square (RMS) roughnesses of 0, 2, 5, and 10% KIdoped perovskite films were found to be 35.26, 38.71, 29.30, DFT calculations were performed within the plane-wave basis and pseudopotential framework (see Supporting Information for details).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the influence of the A-site cation on the band gap is less direct compared to that of the X-site and B-site ions, aligning with our observed results for the band gap. 39 The surface morphology of K + -doped FAPbI 3 films was characterized using atomic force microscopy (AFM) (see Figure S8). The root-mean-square (RMS) roughnesses of 0, 2, 5, and 10% KIdoped perovskite films were found to be 35.26, 38.71, 29.30, DFT calculations were performed within the plane-wave basis and pseudopotential framework (see Supporting Information for details).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the very low formation energy of K FA indicates that the doped K + ion can be located not only at the surfaces of grains as suggested by previous studies 42 but also in the energetically favorable points in the FAPbI 3 lattice. On the other hand, Kubicki et al, who investigated the microstructure of phases of KI-doped lead halide perovskites via 39 K Solid-State NMR, found that K + is not incorporated into the perovskite lattice. 29 Therefore, more work regarding the NMR of thin film K-doped FAPbI 3 needs to be carried out in the future to confirm the presence of K cations within the perovskite structure utilizing solid-state NMR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Urbach energy is a popular structural characteristic representing energetic disorder in crystalline (e.g., GaAs, Si, MAPbI 3 , CIGS) , and also semicrystalline (such as organic) semiconductors for optoelectronic applications. , The relevance of the Urbach energy manifests itself in its correlation with structural and optoelectronic properties and thus also with optoelectronic functionality. ,, For example, the Urbach energy is related to the minimal open-circuit-voltage deficit achievable when a semiconductor is used for solar cell applications. ,,,, Accordingly, the Urbach energy is a valuable figure of merit, expressing the performance potential of present and future semiconductor materials in a single number …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] ; These various optoelectronic properties can be modified by changing the composition of A, B, and X ions in perovskite structure. [5][6][7] Application of perovskite materials as the light harvesting films has significantly increased the power conversion efficiency (PCE) of corresponding cells from 3.8% in 2009 to 26.08%. [8][9][10][11][12] The rapid progress in efficiency of PSCs has indicated that deposition techniques for the light-absorbing film, the electron transporting layers (ETLs) and hole transporting layers (HTLs), have extreme effects on related uniformity and surface quality, resulting in high efficiency and stability of the devices.…”
Section: Introductionmentioning
confidence: 99%